Prey availability and accessibility drive hunter movement. Issue 1 (8th July 2019) - Wszola, Lyndsie S.; Stuber, Erica F.; Chizinski, Christopher J.; Lusk, Jeffrey J.; Fontaine, Joseph J.
Abstract : A growing body of evidence suggests that hunter effort varies temporally and spatially, affecting game populations in unexpected ways. We set out to identify sources of variation in the spatial distribution of hunter effort by ring‐necked pheasant Phasianus colchicus hunters during two time periods representing different spatial decisions: where to access a hunting location at the start of a hunt and where to hunt within it for the duration of the hunt. Pheasant hunters used direct and indirect information about the availability and accessibility of pheasants to make spatial decisions throughout their hunts, but the sources of information used at the beginning of hunts differed from those used for the duration of hunts. Hunter access point effort at the start of hunts was positively associated with proximity to public access signs and declined near marked safety zones around occupied structures and livestock, indicating that hunters responded to the spatial distribution and information content of public access infrastructure. Hunter effort within fields for the duration of hunts was positively related to predicted pheasant habitat use and negatively associated with correlates of physical exertion and increasing distance from field edges. Our findings indicate that hunters in the field are making spatial decisions in response to information about public land access, their own physical state, and perceived opportunity to encounter pheasants. Our results further suggest managers may be able to optimize public lands for wildlife habitat and recreational value without imposing new regulations by managing the information provided to hunters.